"Reverse Spider View" for left stem coronary artery angiographic evaluation. Issue 2 (13th December 2022) - Rigatelli, Gianluca; Gianese, Filippo; Zuin, Marco; Rodino', Giulio; Marchese, Giuseppe; Pasquetto, Giampaolo
Abstract: Among the angiographic views used to evaluate left coronary system, the so‐called "spider view" represents one of the most iconic, in particular for its ability to evaluate the Left Main stem (LM) and/or to guide percutaneous coronary interventions (PCIs) on LM bifurcation disease. Unfortunately, the use of such view is graved by a high X‐ray exposure for both the operator and the patient. To overcome these limitations, we described an alternative coronary angiographic view, called "reverse spider" which is able to give more information about LM body and bifurcation disease with less X‐ray exposure for the operator.